Physio‐morphological, biochemical, and anatomical traits of drought‐tolerant and susceptible sorghum cultivars under pre‐ and post‐anthesis drought. Issue 2 (5th November 2020) - Akman, Hayati; Zhang, Cankui; Ejeta, Gebisa
Abstract: Understanding the physiological mechanisms that control drought tolerance in crop plants is vital for effective breeding. In this study, we characterized drought stress responses in four sorghum cultivars exhibiting differential levels of drought tolerance at pre‐ and post‐anthesis. Greenhouse‐grown plants were subjected to two types of drought treatment, water stress (WS) and desiccant‐induced water stress (DA), timed to occur at pre‐ and post‐anthesis. Multiple physiological measurements were then made revealing varying responses among the experimental cultivars. The pre‐ and post‐flowering drought‐tolerant cultivar P898012 showed a significantly higher net photosynthetic rate, higher transpiration rate, and greater stomatal conductance compared to the drought‐susceptible cultivars at both pre‐ and post‐anthesis. A significantly greater stomatal size was also detected in P898012, while the highest stomatal density was found in the drought‐susceptible cultivar P721Q. Meanwhile, the two post‐flowering drought‐tolerant cultivars P898082 and B35 had a higher starch content and exhibited greater osmotic potential under post‐anthesis water stress. Compared to WS and well‐watered control plants, a greater increase in root biomass was observed in P898012 under DA at pre‐anthesis. This finding suggests that plants invested more assimilates into the roots under severe DA at pre‐anthesis. Overall, our results show good conformity between drought tolerance in sorghum and key physiological mechanisms of stomatal conductance, root growth patterns, and starch accumulation, all of which act as coping mechanisms during critical drought‐sensitive growth stages.